Humanistic Learning Ecology in Global Digital Classrooms - Oliver James Bennett; Lucas Andrew Foster (Innovate Inovation Teaching And Learning, 2026)
This study examines the enactment of humanistic learning ecology within global digital classrooms, exploring how Indonesian higher education institutions nurture whole-person development amid accelerating digital globalisation. The research background is grounded in the tension between efficiency-driven technological integration and the humanistic imperative to foster empathy, dignity, and meaningful interpersonal connections in learning. Employing a qualitative grounded-theory design, data were collected over eleven months from 30 participants across four universities through in-depth interviews, ecological mapping exercises, reflective diaries, and digital classroom observations. Findings reveal three constitutive dimensions of humanistic digital learning ecology: the cultivation of empathic digital presence, the co-creation of culturally resonant learning spaces, and the integration of contemplative practices in digitally mediated instruction. The study concludes that humanistic learning ecology flourishes only when institutions balance technological affordance with relational intentionality and cultural sensitivity. Recommendations are provided for curriculum designers, institutional leaders, and policymakers committed to humane digital education futures.